2009
DOI: 10.1097/bpo.0b013e3181b76985
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Proximal Bifurcation of the Femur

Abstract: We present a case report of a boy with a unilateral bifurcation of the proximal femur with a bifid femoral neck and 2 femoral heads. The patient had no other musculoskeletal or neurovascular abnormalities. One femoral head articulated with the acetabulum but the nonarticulating, larger head was better developed. The articulating head and neck were resected and the nonarticulating head was reduced. This hip then continued to develop well. This is the first report of such a phenomenon in the scientific literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Osuji et al 7 reported a patient presenting proximal duplication of the femur who underwent excision of one of the heads and neck of the femur associated with a defeat osteotomy, Salter-type pelvic osteotomy, and adductor tenotomy due to the remaining 70°anteversion of the femoral head. Compared to the present case, complete excision of the femur was not an option, as the lateral part formed the lateral condyle of the femur, and the medial part, the head and neck of the femur.…”
Section: Discussionmentioning
confidence: 99%
“…Osuji et al 7 reported a patient presenting proximal duplication of the femur who underwent excision of one of the heads and neck of the femur associated with a defeat osteotomy, Salter-type pelvic osteotomy, and adductor tenotomy due to the remaining 70°anteversion of the femoral head. Compared to the present case, complete excision of the femur was not an option, as the lateral part formed the lateral condyle of the femur, and the medial part, the head and neck of the femur.…”
Section: Discussionmentioning
confidence: 99%
“…The femur almost always bifurcates at its distal end [13]; only one case of proximal duplication (two femoral heads and necks) has been reported up to now [14]. Duplication of the femur results in a more or less pronounced shortening of the thigh.…”
Section: Duplication Of the Femurmentioning
confidence: 99%